Fractional Order SMC Design to Enhance the Dynamic Stability of PV Systems During Unexpected Network Events - Nafiz Musarrat, Md; Fekih, Afef (Proceedings of the American Control Conference, 2022)
This paper designs and implements a fractional order sliding mode approach (FOSMC) for grid-tied photovoltaic (PV) systems. The proposed FOSMC is derived based on a novel sliding manifold that takes into account the estimates of the unmatched disturbances. Its main objective is to control the dc-link voltage and enhance its dynamic response during unexpected network events. System stability is assessed using the Lyapunov theory. The performance of the proposed FOSMC is assessed using a grid-tied PV system subject to temporary symmetrical grid faults, steep load variations and mismatched disturbances. Comparison analysis with a standard SMC approach (SSMC) is also carried over. The obtained results revealed the superior performance of the proposed approach in improving the transient stability of dc-link voltage during grid faulty conditions. Additionally, the FOSMC was found to have faster time response and stronger robustness against network disturbances than the SSMC.